2021
DOI: 10.1128/jb.00652-20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spermidine on Biofilm Formation in Escherichia coli K-12

Abstract: Polyamines are essential for biofilm formation in Escherichia coli, but it is still unclear which polyamines are primarily responsible for this phenomenon. To address this issue, we constructed a series of E. coli K-12 strains with mutations in genes required for the synthesis and metabolism of polyamines. Disruption of the spermidine synthase gene (speE) caused a severe defect in biofilm formation. This defect was rescued by the addition of spermidine to the medium, but not by putrescine or cadaverine. A mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…of lptF results in a filamenting phenotype increased sensitivity to hydrophobic antibiotics and an altered form of lipopolysaccharides [28]. The potABCD operon encodes a polyamine (putrescine/spermidine) transport system [29]. In both eukaryotes and prokaryotes, normal growth and multiplication are completely dependent on polyamines [30].…”
Section: Resultsmentioning
confidence: 99%
“…of lptF results in a filamenting phenotype increased sensitivity to hydrophobic antibiotics and an altered form of lipopolysaccharides [28]. The potABCD operon encodes a polyamine (putrescine/spermidine) transport system [29]. In both eukaryotes and prokaryotes, normal growth and multiplication are completely dependent on polyamines [30].…”
Section: Resultsmentioning
confidence: 99%
“…The instrument was used as previously described. 28 Values are the averages of three independent cultures ± standard deviations.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…After passing through the Millex-LH filter, the filtrates were subjected to HPLC analysis as described previously. 28,29 Isolation of the Intermediate from the Cells of Strain YF48. For preculture, 10 mL of LB medium containing 100 μg/mL of ampicillin in 100 mL Erlenmeyer flasks was inoculated with a single colony of strain YF48.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The chromosomal genes speD, and argR were replaced with FRT (FLP recombination target)- kan R -FRT from the Keio gene knockout collection (Baba et al 2006 ) by P1 vir transduction (Miller 1972 ). The disruption of speG , potE, and the ATP binding site of the puuA gene were described previously (Kurihara et al 2008 , 2009b ; Thongbhubate et al 2021 ). The patA and potFGHI genes were disrupted by a method described previously (Datsenko and Wanner 2000 ) using pKD13 as a template for the PCR amplification with delta-ygjG F and delta-ygjG R as primers for patA , and potF-up and potI-down as primers for potFGHI (Additional file 1 : Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Two spermidine transporters, PotABCD and MdtJI, and six putrescine transporters, PuuP, YdcSTUV, PlaP, PotE, PotFGHI, and SapBCDF, have been identified (Kashiwagi et al 1992 ; Pistocchi et al 1993 ; Kurihara et al 2009a , b ; Kurihara et al 2011 ; Saier et al 2016 ; Sugiyama et al 2016 ). We recently reported that PotFGHI can import spermidine under biofilm-forming conditions (Thongbhubate et al 2021 ).
Fig.
…”
Section: Introductionmentioning
confidence: 99%